Filmer le travail : un travail du sociologue ? - Jean-Paul Gehin (La Nouvelle Revue du Travail)
Filmer le travail is both a thematic film festival, a place for reflection on the use of images and movies, for social sciences and cultural mediation assembly allowing public debates on the evolution of contemporary work. To analyze this unusual experience being a (very) participating observer, I will examine a group of texts on the history since 1950 of the use of images by the sociology of work in France. Three periods can be identified: the 1960s during which the use of images for research purposes is of significant but marginal concern in the institutionalization of the sociology of work in France; 1980-1990, defined by careful experimentation and a constricted reflection; the 2000s, which saw the development of practices (which remain minority) involving the Valorisation of the image (especially audiovisual) in the research process and a stronger link to creative documentary.